Correlates of susceptibility to smoking among Mexican origin youth residing in Houston, Texas: A cross-sectional analysis - Prokhorov Alexander V; Bondy Melissa L; Vasudevan Vandita; Waters Andrew J; Wilkinson Anna V; Spitz Margaret R (BMC, 2008)
Abstract Background Survey data suggest that in Texas Latino youth exhibit higher rates of susceptibility to smoking than youth from other ethnic groups. In this analysis we examined the relationship between susceptibility to smoking and well-known risk factors associated with smoking initiation among a cohort of 11 to 13 year old Mexican origin youth residing in Houston, Texas. Methods We analyzed cross-sectional survey data from 1,187 participants who reported they had never smoked, even a puff of a cigarette. The survey assessed peer and family social influence, school and neighborhood characteristics, level of family acculturation and socioeconomic status, and attitudes toward smoking. Bivariate associations, Student's t-tests, and logistic regression analysis were used to examine predictors of susceptibility. Results Overall, 22.1% of the never-smokers were susceptible to smoking. Boys were more likely to be susceptible than girls (25.6% vs. 18.9%), and susceptible children were slightly older than non-susceptible children (12.1 vs. 11.8 years). In addition, multivariate analyses revealed that positive expectations about smoking exerted the strongest influence on susceptibility status (odds ratio = 4.85). Multivariate analyses further revealed that compared to non-susceptible participants, susceptibles were more likely to report peer influences supportive of smoking, lower subjective social status and more detentions at school, more temptations to try smoking and to have a mother and a brother who smokes. Conclusion Our findings suggest that interventions that target positive expectations about smoking may be useful in this population. Furthermore, because youth encounter smoking-initiation risk factors in different social environments, our results underscore the continued need for both family- and school-based primary prevention programs to adequately combat their influence. The results also can be used to inform the development of culturally sensitive programs for Mexican origin youth.